2017
DOI: 10.3174/ajnr.a5070
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Defined Oligodendroglioma Is Characterized by Indistinct Tumor Borders at MRI

Abstract: BACKGROUND AND PURPOSE:In 2016, the World Health Organization revised the brain tumor classification, making IDH mutation and 1p/19q codeletion the defining features of oligodendroglioma. To determine whether imaging characteristics previously associated with oligodendroglial tumors are still applicable, we evaluated the MR imaging features of genetically defined oligodendrogliomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 27 publications
(32 reference statements)
2
41
0
2
Order By: Relevance
“…LGGs from the TCGA/TCIA and NYU databases distributed by histopathologic assignment and the presence or absence of the T2-FLAIR mismatch sign also more frequently display sharp margins, homogenous internal signal intensity, and lesser degree of contrast enhancement when compared with IDH-wild type lesions (26)(27)(28). IDHmut-Codel and IDHmut-Noncodel gliomas appear to differ with respect to tumor margins and internal heterogeneity (29). Nonetheless, it is generally accepted that conventional MRI findings do not possess sufficient specificity to predict the underlying histologic or molecular subtype of an LGG in an individual patient (30).…”
Section: Discussionmentioning
confidence: 95%
“…LGGs from the TCGA/TCIA and NYU databases distributed by histopathologic assignment and the presence or absence of the T2-FLAIR mismatch sign also more frequently display sharp margins, homogenous internal signal intensity, and lesser degree of contrast enhancement when compared with IDH-wild type lesions (26)(27)(28). IDHmut-Codel and IDHmut-Noncodel gliomas appear to differ with respect to tumor margins and internal heterogeneity (29). Nonetheless, it is generally accepted that conventional MRI findings do not possess sufficient specificity to predict the underlying histologic or molecular subtype of an LGG in an individual patient (30).…”
Section: Discussionmentioning
confidence: 95%
“…Johnson et al 6 have shown that noncircumscribed borders correlate with 1p/19q codeletion, but given that this appearance was also present in 45% of noncodeleted tumors, this MR imaging feature is not sufficiently specific to predict codeletion with confidence. Rather, to predict 1p/19q status with high specificity, it may be more useful to use circumscribed borders as predictive of a noncodeleted tumor, albeit with limited sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the presence of calcification on CT has been found to predict 1p/19q loss of heterozygosity. 5 Noncircumscribed borders have also been shown to correlate with 1p/19q codeletion, occurring in 92% of molecular oligodendrogliomas in a recent series by Johnson et al, 6 but this appearance is not specific because it was also present in 45% of noncodeleted tumors. Other conventional imaging features suggested as being typical of oligodendrogliomas include a cortical-subcortical location, 7 though it is not clear whether this remains true in the current molecular era.…”
mentioning
confidence: 99%
“…4 Finally, the ADC value has previously been reported to predict 1p/19q codeletion status, a marker of oligodendroglioma, in lower grade gliomas. 35,41 In the study by Johnson et al, 41 the ADC values were calculated from sampling both the highest and lowest ADC areas. However, we did not detect a significant correlation between rADC values and 1p/19q codeletion status.…”
Section: Discussionmentioning
confidence: 99%